The Use of Functional Electrical Stimulation on the Upper Limb and Interscapular Muscles of Patients with Stroke for the Improvement of Reaching Movements: A Feasibility Study - Cuesta-Gómez, Alicia; Molina-Rueda, Francisco; Carratala-Tejada, Maria; Imatz-Ojanguren, Eukene; Torricelli, Diego; Miangolarra-Page, Juan Carlos (Frontiers in Neurology, 2017)
Introduction. Reaching movements in stroke patients are characterized by decreased amplitudes at the shoulder and elbow joints and greater displacements of the trunk, compared to healthy subjects. The importance of an appropriate and specific contraction of the interscapular and upper limb (UL) muscles is crucial to achieving proper reaching movements. Functional electrical stimulation (FES) is used to activate the paretic muscles using short-duration electrical pulses. Objective. To evaluate whether the application of FES in the UL and interscapular muscles of stroke patients with motor impairments of the UL modifies patients’ reaching patterns, measured using instrumental movement analysis systems. Design. A cross-sectional study was carried out. Setting. The VICON Motion System® was used to conduct motion analysis. Participants. 21 patients with chronic stroke. Intervention. The Compex® electric stimulator was used to provide muscle stimulation during two conditions: a placebo condition and a FES condition. Main Outcome Measures. We analyzed the joint kinematics (trunk, shoulder and elbow) from the starting position until the affected hand reached the glass. Results. Participants receiving FES carried out the movement with less trunk flexion, while shoulder flexion elbow extension was increased, compared to placebo conditions. Conclusions. The application of FES to the UL and interscapular muscles of stroke patients with motor impairment of the UL, has improved reaching movements.